IMPLEMENTATION OF EDUCATIONAL MANAGEMENT INFORMATION SYSTEM (SIM-ISLAMIC EDUCATION) IN MADRASAH ADMINISTRATIVE EFFICIENCY - Khafidah, Wahyu; Akyuni, Qurrata; Zulfadli (Program Studi Manajemen Pendidikan Islam, 2026)
This study analyzes the implementation of an Islamic Education Management Information System (ISMS) to improve madrasah administrative efficiency in the era of digital transformation. Using a Systematic Literature Review approach to ten selected journal articles from various trusted academic databases for the 2023-2025 period, this study reveals that digitizing madrasah administration through an ISMS has a significant impact on increasing operational efficiency. The systematic implementation process through the stages of initiation, elaboration, development, and transition showed a product suitability level of 90.29% based on expert validation. The artificial intelligence -based system achieved 95% accuracy in multimodal data processing, surpassing conventional systems which only achieved 80%. The system's effectiveness is proven by reducing administrative burdens, accelerating data processing, increasing information accuracy, and facilitating data-driven decision-making. Supporting factors for success include leadership commitment, adequate digital infrastructure, and human resource readiness. Key challenges faced include the digital divide, limited infrastructure, technophobia , poor internet connectivity, and budget constraints. This study recommends the development of a comprehensive digitalization roadmap , strengthening human resource capacity through ongoing training, and developing a contextual system effectiveness evaluation model to optimize digital transformation in sustainable Islamic education governance